The Differentiation of Human Cytomegalovirus Infected-Monocytes Is Required for Viral Replication - Min, Chan-Ki; Shakya, Akhalesh K.; Lee, Byeong-Jae; Streblow, Daniel N.; Caposio, Patrizia; Yurochko, Andrew D. (Frontiers in Cellular and Infection Microbiology, 2020)
Viral dissemination is a key mechanism responsible for persistence and disease following human cytomegalovirus (HCMV) infection. Monocytes play a pivotal role in viral dissemination to organ tissue during primary infection and following reactivation of the virus in the bone marrow. For example, during primary infection, infected monocytes migrate into various tissues and differentiate into macrophages, which then become a source of persistent viral replication. In addition, because differentiated macrophages can survive for months to years, they provide a potential source of the persistent infection observed in various organ systems. We broadly note that there are three phases to infection and differentiation of HCMV-infected monocytes. 1) Virus enters and traffics to the nucleus through a virus receptor ligand engagement event that activates a unique signalosome in a manner distinct from other cell types infected to initiate monocyte-to-macrophage differentiation. This receptor-ligand event rapidly activates a unique signalosome initiating this differentiation. 2) Following the initial infection, HCMV undergoes a “quiescence-like state” in monocytes for several weeks during which time monocytes are required to differentiate into macrophages. The initial event is triggered by the receptor-ligand engagement, while potential long-term cellular activation is maintained by chronic viral mediated signaling. 3) Once HCMV infected monocytes differentiate into macrophages, the expression of immediate early viral (IE) genes is detectable, followed by viral replication and long term infectious viral particles release. Here, we review the detailed mechanisms of each phase during infection and differentiation into macrophages and discuss the biological significance of the differentiation of monocytes in the pathogenesis of HCMV.